Viral Metagenomics Reveals Diverse Viruses in the Feces Samples of Raccoon Dogs - Yang, Shixing; He, Yumin; Chen, Xu; Kalim, Ullah; Wang, Yan; Yang, Shuyu; Qi, Haifeng; Cheng, HengZheng; Lu, Xiang; Wang, Xiaochun; Shen, Quan; Zhang, Wen (Frontiers in Veterinary Science, 2021)
Raccoon dogs as an ancient species of Canidae are the host of many viruses, including rabies virus, canine distemper virus, severe acute respiratory syndrome coronavirus, and so on. With the development of raccoon dog breeding in recent years, some viruses which infected poultry or pigs were also detected from raccoon dogs. At present, the fecal virome of raccoon dogs has been rarely studied. Using an unbiased viral metagenomic approach, we investigated the fecal virome in raccoon dogs collected from one farm of Jilin Province, China. Many DNA or RNA viruses identified in those fecal samples were mainly from seven families, including Circoviridae, Smacoviridae, Genomoviridae, Parvoviridae, Picornaviridae, Astroviridae, and Hepeviridae. This study increased our understanding of the fecal virome in raccoon dog and provided valuable information for the monitoring, prevention, and treatment of viral diseases of these animals.